Effect of treatment temperature on the initial performance of layers of water-based paints in heat-treated pine and beech wood - Kaymakci, Alperen; Birinci, Emre; Karamanoglu, Mehmet; Kesik, Haci İsmail (BioResources, 2022)
Hardness, surface roughness, and adhesion strength were determined for water-based opaque paints applied to heat-treated wood material surfaces. For this purpose, Scotch pine (Pinus sylvestris L.) and beech (Fagus orientalis Lipsky) woods were used as experimental material. Specimens were subjected to heat treatment at 3 different temperatures (150, 180, and 210 °C) and 2 different periods (2 and 4 h) under laboratory conditions. Two-component water-based paints with commercial codes D17 and D45 were applied to the surfaces. The hardness, surface roughness, and adhesion strength values of painted samples were determined according to the applicable standards. The results showed that there were higher values of hardness and surface roughness of water-based paints in short-term heat treatment compared with long-term heat treatment. A general decrease in pine with D17 and D45 paints applied to the surfaces and in beech with D45 in adhesion strength was detected depending on the increasing heat treatment temperature and duration. An increase was observed in beech samples with D17 paint applied.